Hubungan Konten Promosi Akun Instagram @Kamargadget dengan Minat Beli Followers - Athallah Pratama Putra; Anne Maryani (UNISBA Press, 2022)
Abstract. Instagram is a multi-functional media that can be used in any case and by anyone, especially business people to promote the products and services they sell. Kamar gadget is one of the companies that utilize Instagram social media as a means of promotion with the @kamargadget account. Therefore, this study aims to determine the relationship between the promotional content of the @kamargadget Instagram account and followers' buying interest using correlational methods and quantitative approaches. The data collected is primary data obtained through questionnaires, as well as secondary data obtained through library research. The population in this study is the followers of the @kamargadget account totaling 71,100. To measure the sample, the Slovin formula was used to obtain 100 samples with a percentage rate of 10%. The data analysis technique used is a descriptive and inferential analysis using IBM SPSS Statistics for Windows version 22. The results of this study are that there is a relationship between aspects of Personal Relevance with followers' buying interest with the Spearman Test of 0.549. There is a relationship between the Interactivity aspect and the buying interest of followers with the Spearman Test of 0.471. There is a relationship between the Message aspect and followers' buying interest with the Spearman Test of 0.437. There is a relationship between Brand Familiarity and followers' buying interest with the Spearman Test of 0.359. So that the simultaneous relationship between @kamargadget Promotional Content and followers' buying interest is 0.581. Abstrak. Instagram sebuah media multi fungsi yang dapat digunakan dalam hal apapun dan oleh siapapun terutama para pembisnis untuk mempromosikan produk serta layanan yang mereka jual. Kamar gadget adalah salah satu perusahaan yang memanfaatkan media sosial Instagram sebagai sarana promosi dengan akun @kamargadget. Oleh karena itu, penelitian ini bertujuan untuk mengetahui hubungan antara konten promosi akun Instagram @kamargadget dengan minat beli followers dengan menggunakan metode korelasional dan pendekatan kuantitatif. Data yang dikumpulkan merupakan data primer yang didapatkan melalui kuesioner, serta data sekunder yang didapatkan melalui studi kepustakaan. Populasi dalam penelitian ini adalah followers akun @kamargadget berjumlah 71.100. Untuk mengukur sampel digunakan rumus Slovin sehingga diperoleh 100 sampel dengan tingkat persentase 10%. Teknik analisis data yang digunakan yaitu analisis deskriptif dan inferensial menggunakan IBM SPSS Statistic untuk Windows versi 22. Hasil penelitian ini adalah terdapat hubungan antara aspek Personal Relevance dengan minat beli followers dengan Uji Spearman sebesar 0,549. Terdapat hubungan antara aspek Interactivity dengan minat beli followers dengan Uji Spearman sebesar 0,471. Terdapat hubungan antara aspek Message dengan minat beli followers dengan Uji Spearman sebesar 0,437. Terdapat hubungan antara Brand Familirity dengan minat beli followers dengan Uji Spearman sebesar 0,359. Sehingga hubungan secara simultan antara Konten Promosi @kamargadget dengan minat beli followers yaitu 0,581.